Third Sector Organization A Needed Look at the Artistic-Cultural Organization - Sukel, W. M. (Academy of Management Review, 1978)
The article discusses management of cultural organizations and the abstruse goals such as artistic performance or fund raising that can be difficult to evaluate in terms of organizational profitability. Suggestions for improved operation of third sector organizations include communicating goals to the smaller organizational units, making public goals the operative goals in departments, using constraints in the assessment phase, resolving the difference between desired and feasible goals, adding weighting to various goals, accepting input from the staff, and maintaining flexibility in the whole organization.